1986
DOI: 10.1213/00000539-198612000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Epinephrine Reduces Systemic Absorption of Extradural Diacetylmorphine

Abstract: HJ. Epinephrine reduces systemic absorption of extradural diacetylmorphine. Anesth Analg 1986;65:1290-4.The effect of epinephriiie on the vascular absorption of morphine froin the extradural space is uncertain; this study examined the effect of epinephrine on the related but more lipophilic opiate diacetylmorphine (diamorphine, heroin) because any effects of vasoconstriction on diacetylmorphirze absorption should be maxirnally apparent. With this experiment, we hoped to resolve whether epinephrine does or does… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Differences between these two groups were not significant at any time of measurement. By causing vasoconstriction of the extradural veins, adrenaline decreases the amount of diamorphine absorbed systemically [11], thus effectively increasing the concentration available in the extradural space and thus we expected more prolonged analgesia in the women receiving adrenaline. The small numbers in each group may account for why we did not find this.…”
Section: Discussionmentioning
confidence: 86%
“…Differences between these two groups were not significant at any time of measurement. By causing vasoconstriction of the extradural veins, adrenaline decreases the amount of diamorphine absorbed systemically [11], thus effectively increasing the concentration available in the extradural space and thus we expected more prolonged analgesia in the women receiving adrenaline. The small numbers in each group may account for why we did not find this.…”
Section: Discussionmentioning
confidence: 86%
“…In our previous study, we found that adding adrenaline to a single dose of epidural pethidine had significant advantages [9]. By producing vasoconstriction in the epidural space, adrenaline is thought to reduce the rate of vascular absorption and enhance transfer of drugs across the dura [11, 12]. Also, stimulation of α 2 ‐adrenoceptors in the spinal cord has a direct analgesic effect [11].…”
Section: Discussionmentioning
confidence: 99%
“…Following epidural administration, in order to reach the site of action the local anesthetic needs to cross the spinal meninges [7]. It can either be taken up by the epidural fat, resorbed into the systemic circulation via venous blood vessels, or cross the dura mater and enter the cerebrospinal fl uid [8]. Adrenergic agonists have been frequently combined with local anesthetics to prolong the motor -sensory block through the supposed mechanism of decreasing epidural blood fl ow and by causing antinociceptive effects via interaction with alpha-2-adrenoceptors located in the brain and spinal cord [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%